Intracardiac hemodynemics, fibroblast growth factor-2 and oxyproline levels with mitral valve prolapse in combination with type 1 diabetes mellitus - Olena Nikolenko; Oleksii Korzh (Kazimierz Wielki University, 2020)
The purpose. The aim of the study was a comparative analysis of basic echocardiographic parameters, fibroblast growth factor-2 and free and peptide-bounding oxyproline indicators in young patients with mitral valve prolapse, type 1 diabetes mellitus and the combination of both indications. Materials and methods. 93 patients between 19 and 33 years old with either mitral valve prolapse, type 1 diabetes and the combination of both indications were examined.  There are 24 people with diagnosed mitral valve prolapse, 33 patients with type 1 diabetes mellitus and mitral valve prolapse and 36 patients with the monomorbid type 1 diabetes mellitus. The establishment of the diagnosis of mitral valve prolapse implemented by echocardiographic criteria L. Freed et al. (2002). The concentration of fibroblast growth factor-2 in blood plasma was determined by the enzyme immunoassay using a Quantikine reagent kit (Human FGF basic Immunoassay), manufactured by R&D Systems, Inc. (USA) and expressed in pg/ml. Free and peptide-bounding oxyproline as the markers of connective tissue metabolism were determined by the method of P. N. Sharaev and expressed in µmol/L. Results. In patients with mitral valve prolapse and ype 1 diabetes mellitus, the higher values of l left ventricular posterior wall thickness and intraventricular septum have been revealed in comparison with the groups of patients with monomorbid mitral valve prolapse and ype 1 diabetes mellitus. Fibroblast growth factor-2 was higher in group with combination of both indications, where it was [23.7 ± 0.25] pg/ml compared to the control group [14.20 ± 0.22] pg/ml (p <0.01). There was also a significant difference in the levels of fibroblast growth factor-2 between group with either mitral valve prolapse [15.33 ±0.24] pg/ml and combination of mitral valve prolapse and type 1 diabetes [23.71 ±0.25] pg/ml (p<0.01). The level of peptide-bound oxyproline, just as the level of free oxyproline, significantly increased in patients with comorbid pathology, compared to the control group: [16.06 ±1.54] µmol/l versus [8.7 ±0.81] µmol/l (p<0.01) respectively.  Conclusions. The most significant differences in the indices of intracardiac hemodynamics, fibroblast growth factor-2 and free and peptide-bounding oxyproline compared with control were observed in patients with combination of mitral valve prolapse and type 1 diabetes, which may indicate the influence of diabetic metabolic processes on further structural changes in the mitral valve.